Effect of weave parameters on the mechanical properties of 3D woven glass composites. (1st September 2019) - Dahale, Monali; Neale, Geoffrey; Lupicini, Ranieri; Cascone, Lucio; McGarrigle, Cormac; Kelly, John; Archer, Edward; Harkin-Jones, Eileen; McIlhagger, Alistair
Abstract: Due to the complex structure of 3D woven fabrics, their mechanical properties and failure modes tend to deviate from that of conventional equivalent 2D woven and unidirectional fabric composites. A lack of in-depth understanding of the relationships between the weave parameters and mechanical properties of 3D woven composite materials has inspired this investigation. This paper presents a comprehensive experimental study of the effect of pick density on the mechanical properties such as tension, compression, short beam shear and Izod impact energy in 3D layer-to-layer glass/epoxy woven composite structures. The 3D woven fabrics are manufactured in two different pick density extremes: 4 and 14 picks/cm with a constant end density of 12 ends/cm from Hybon 2002 E glass fibres. The mechanical properties were improved by the decrease in waviness and misalignment of the load carrying fibres. An interesting observation which has never been seen before was made in lower pick density specimens under tensile loading. Severe diagonal crack propagation because of strain-induced shear failure was observed and attributed to influence of the movement of misaligned yarns with increasing tensile strain. This study has helped in deriving a relationship between the weave parameters and the in-plane mechanical properties and expected failure in this 3D woven layer-to-layer warp interlock glass fabric.